Deformation twinning via the motion of adjacent dislocations in a nanostructured CoCrFeNi high-entropy alloy. Issue 18 (23rd August 2022) - Zhai, Jinpo; Yan, Zhigang; Yu, Hao
Abstract : A three-layer twin with two incoherent twin boundaries was identified using high-resolution transmission electron microscopy, and its twinning mechanism was analyzed. Twinning is formed by dissociated dislocations meeting on the adjacent slip plane. Abstract : Deformation twinning was observed in a nanostructured CoCrFeNi high-entropy alloy processed by cold rolling. A three-layer twin with two incoherent twin boundaries was identified using high-resolution transmission electron microscopy, and its twinning mechanism was analyzed. Twinning is formed by dissociated dislocations meeting on the adjacent slip plane. This twinning mechanism possibly works for low-SF materials with high dislocation density.